The Role of Brand Image, Brand Ambassadors and Korean Wave on Intention to Purchase of K-popers Customers - Tannady, Hendy; Maulidna, Adelia Putri (Journal of Social Science and Business Studies, 2024)
The purpose of this study is to investigate how brand ambassadors and the Korean wave affect brand perception and how that affects consumer choice. Using non-probability selection approaches, a sample of 100 respondents was chosen from a population of K-poppers as part of this quantitative research study. Direct data searches, online research, and questionnaires were used to gather data. Structural equation modeling (SEM) statistical approaches are used in data analysis. The analysis's findings indicate that neither the Korean wave nor brand ambassadors alone significantly affect a company's reputation. Together, nevertheless, they significantly and favorably impact brand image. In addition, the Korean wave and brand image, as well as brand ambassadors, have a big impact on buying decisions. In general, the Korean wave and brand ambassadors have a big impact on brand perception and can influence consumer decisions separately or in tandem. These findings highlight the value of using brand ambassadors and the Korean wave in marketing tactics to create a strong brand identity and influence consumer decisions to buy, particularly among K-pop enthusiasts.